Phenotypic stability for kernel yield in groundnut (Arachis hypogaea L.) - A. Mothilal, P. Vindhiya varman and N. Manivannan (Electronic Journal of Plant Breeding, 2010)
The yield stability of 16 Spanish bunch groundnut genotypes were evaluated in four seasons consecutively forkernel yield per hectare. Two genotypes viz., ICGV 92206 and ICGV 93392 were found to be stable for kernelyield as they possessed non-significant deviation from the regression with regression coefficient nearing unity.